Tantangan minimnya literasi informasi pada gen z dan peran pustakawan perguruan tinggi di era digital - asiyah, asiyah (Maliki Interdisciplinary Journal, 2026)
The low level of information literacy among Generation Z poses a significant challenge in higher education environments in Indonesia. Although students have vast access to information, many still lack the ability to select, evaluate, and verify information effectively. This study analyzes the causes of low information literacy among students and highlights the strategic role of academic librarians in enhancing these skills. Using a literature study method, this research examines national references, scholarly articles, and institutional research, including sources from UIN Maulana Malik Ibrahim Malang’s repository. The results indicate that Generation Z relies heavily on search engines and social media without considering the validity of information. Furthermore, limited literacy training, insufficient instructional support, and a weak reading culture worsen the situation. Academic librarians play an essential role through information literacy programs, academic interventions, faculty collaboration, and digital library services. This literature review concludes that improving students’ information literacy requires integrative and sustainable strategies, especially by strengthening librarians’ roles as literacy educators and academic partners.